An African Alternative to Western Cosmological Argument Hopeless Reliance on Ontological Argument - Kiatezua Lubanzadio Luyaluka (RIRAI Publisher, 2020)
This paper demonstrates that as used in Western philosophy cosmological argument relies on ontological argument to jump to its conclusion about the existence of a Supreme-being-creator. Pointing to the failure of the Western cosmological argument, the paper shows that either creation happens within the creator or outside of him. In the first case, the Supreme-being-creator is not immutable; hence, he is not perfect. In the second case a greater being can be conceived which includes creator and creation. Therefore, the Western cosmological argument hopelessly relies on ontological argument to anticipate a priori that the first cause of its conclusion is God, the greatest possible being and a being of maximum perfection. As an alternative to this debunked cosmological argument, this paper offers the kemetic cosmological argument as a valid demonstration of the existence of a Supreme Being absolutely immutable and who is the greatest possible being